Tazkiyat Al-Nafs dalam Penegakan Hukum : Kajian Pemikiran Al-Ghazali - Adhi Pratama, Finsa; Nur Qadar Ar. Razak, Aris; Habibullah, Habibullah; Qosim, Nanang; Asrianto Zainal, Muh; Ode Muhammad Iman Abdi Anantomo Uke, La (Zawiyah: Jurnal Pemikiran Islam, 2025)
Justice serves as a fundamental pillar for Indonesia as a state based on law; however, its implementation still faces disparities in access to the principle of equality before the law. Although numerous studies on justice have been conducted (Hayat, 2020; Sanuri, 2021; Kurniawan et al., 2021; Ibrahim, 2025) from various perspectives—such as positive law, maqāṣid al-sharī‘ah, and moral education—few have examined the issue comprehensively by integrating the classical spiritual-moral value of tazkiyat al-nafs (purification of the soul). This study opens a space to explore the relevance of al-Ghazali’s concept of justice in addressing contemporary issues of justice in Indonesia. Grounded in this premise, the study aims to (1) elaborate al-Ghazali’s theory of justice within its legal dimensions and (2) analyze its potential application in the Indonesian context. The research employs a qualitative-normative method using library research on classical texts and secondary literature, combined with content analysis and philosophical hermeneutics to relate textual insights to Indonesia’s contemporary realities. The findings reveal that al-Ghazali conceives justice as the equilibrium of the soul, the embodiment of just leadership, and the enforcement of law characterized by trustworthiness and transparency. In the Indonesian context, this conception is highly relevant to efforts in reducing poverty, addressing inequality, strengthening political integrity, and enhancing legal transparency. Al-Ghazali’s notion of justice thus offers an ethical paradigm for the development of Indonesia’s legal, political, and economic systems—aimed at realizing a just, civilized, and welfare-oriented society.